Disentangling the Sudanonautes granulatus (Balss, 1929) species complex (Potamoidea: Potamonautidae), with the description of two new freshwater crabs from Nigeria and Côte d’Ivoire, West Africa - Cumberlidge, Neil; Ndongo, Pierre A. Mvogo; Clark, Paul F. (Zootaxa, 2021)
The taxonomic status of the widely distributed West and Central African freshwater crab Sudanonautes granulatus (Balss, 1929) sensu lato is revised in the light of improved morphological evidence which indicates that this taxon is a complex comprising at least 4 species: Sudanonautes granulatus (Balss, 1929) sensu stricto from Togo, S. koudougou n. sp. from Côte d’Ivoire, S. umaji n. sp. from Nigeria, and S. tiko from Cameroon, Nigeria, and Bioko. Diagnoses, illustrations and distribution maps are provided for these species and they are compared with congeners from West and Central Africa.